2019
DOI: 10.1002/jcp.29357
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a prognostic alternative splicing signature in oral squamous cell carcinoma

Abstract: Alternative splicing (AS) is critically associated with tumorigenesis and patient's prognosis.Here, we systematically analyzed survival-associated AS signatures in oral squamous cell carcinoma (OSCC) and evaluated their prognostic predictive values. Survival-related AS events were identified by univariate and multivariate Cox regression analyses using OSCC data from the TCGA head neck squamous cell carcinoma data set. The Percent Spliced In calculated by SpliceSeq from 0 to 1 was used to quantify seven types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…However, LINC00662 had no regulatory effects on hnRNPC expression. hnRNPC is a survival-related splicing factor in OSCC [18], and served as the tumor facilitator in non-small cell lung cancer [33], ovarian cancer [16]. The hnRNPC protein is one of the Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, LINC00662 had no regulatory effects on hnRNPC expression. hnRNPC is a survival-related splicing factor in OSCC [18], and served as the tumor facilitator in non-small cell lung cancer [33], ovarian cancer [16]. The hnRNPC protein is one of the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In past researches, hnRNPC has been illustrated as pivotal mediators in human diseases, including carcinomas [16,17]. Besides, hnRNPC is identified as survival-related splicing factor in OSCC [18]. However, the specific functional role and underlying mechanism of hnRNPC in OSCC was uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study also develops an AS-based prognostic model with good performance (AUC = 0.891 and 0.70 for training and validation cohort, respectively) ( 20 ). However, the TCGA OSCC cohort is randomly and equally split into the training and the validation cohort in this former analysis, which is not recommended in the TROPORT statement ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our research focused on the prognostic significance of AS events in sarcoma patients. Although the prognostic ability of AS events have been widely confirmed in other cancers [ 14 , 19 – 23 , 34 36 ], the association of AS events in sarcoma patients remains unclear. In our study, 1945 AS events were determined as OS-related AS events and 1831 AS events were determined as DFS-related AS events.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, with the development of high-throughput sequencing, many studies have focused on comprehensive genome-wide profiling of AS events in cancer and confirmed that AS events can be used as robust prognostic biomarkers. For example, Zhang et al [ 19 ] studied 330 oral squamous cell carcinoma patients, and a AS event-based signature was established and validated. In addition, the AS-splicing factor (SF) regulatory network was also established.…”
Section: Introductionmentioning
confidence: 99%